Regional Inspectorate Strategies for Achieving Good Governance in Bogor Regency West Java Province - Nanang Suryana; Hyronimus Rowa; Faria Ruhana (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The implementation of good governance is essential for creating an effective, transparent, accountable, and corruption-free government system. As the Government Internal Supervisory Apparatus (APIP), the Bogor Regency Inspectorate plays a strategic role through supervisory, consultative, guidance, and preventive functions. However, supervisory implementation still faces challenges, including limited human resources, high workloads, differences in audit perceptions, and the suboptimal expansion of supervisory functions. This study aims to analyze the strategies implemented by the Bogor Regency Inspectorate in achieving good governance, identify supporting and inhibiting factors, and examine efforts to overcome existing obstacles. This study is based on the good governance framework developed by the United Nations Development Programme (UNDP, 1997) and SWOT analysis theory proposed by Rangkuti (2016). A qualitative method with a descriptive approach was employed. Data were collected through interviews, observations, and documentation, then analyzed using the SWOT framework. The findings show that the Bogor Regency Inspectorate has implemented S-O, W-O, S-T, and W-T strategies through preventive, consultative, guidance, and risk-based supervision approaches. Supporting factors include regulatory support, competent human resources, inter-agency cooperation, SPIP implementation, and bureaucratic reform. Inhibiting factors include the limited number of auditors and PPUPD personnel, high workloads, differences in audit perceptions, and the limited expansion of supervisory functions. Efforts to address these challenges include strengthening APIP capability, improving human resource quality, digitalizing supervisory processes, reinforcing SPIP implementation, applying risk management, and enhancing collaboration with external supervisory institutions. These strategies contribute to strengthening the Inspectorate’s role in supporting the realization of good governance in Bogor Regency.